Production and Income Risk Analysis for the Development of Rice Farming Insurance in Baruga District, Kendari City - Aiman, Andi Muhammad Fawwaz; Bafadal, Azhar; Abdullah, Weka Gusmiarty (International Journal of Technology and Education Research, 2026)
This research aims to determine the production risk and income risk in lowland rice farming and how the production risk compares with the basis for determining premiums for the development of lowland rice farming insurance in Baruga District, Kendari City. This research uses descriptive methods and a quantitative research approach using Variance coefficient analysis.The sampling method in this research is using a purposive sampling method, where the sampling technique takes certain considerations based on the fact that the sample for this research only selected all participants in lowland rice farming insurance, a total of 40 farmers. The results of this research show that (1) the average of rice farming production in Baruga District, Kendari City is 9.020 Kg/Ha/Year and the income risk is IDR 27.602.214 IDR/Ha/Year. The coefficient of variation of production risk is less than 0.5 (0.15 < 0.5) and the coefficient of variation of income risk is less than 0.5 (0.0.3 < 0.5) which indicates that the risk faced is low and the lower limit result is > 0 (6.274) > 0 so this result shows that farmers will always make a profit. (2) Comparison between production risk and the basis for determining premiums for developing agricultural insurance in determining the total premium which remains the same in each planting season even though the level of production risk is different in each planting season. Farmers receive full protection of IDR6,000,000/Ha/MT if there is a risk that causes crop failure